2020
DOI: 10.1002/jez.2415
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids, energy metabolites, and immunity vary across allostatic states for plateau side‐blotched lizards (Uta stansburiana uniformis) residing in a heterogeneous thermal environment

Abstract: Reptiles rely on thermal heat exchange to achieve body temperatures (Tbody) conducive to maintaining homeostasis. Diurnal changes in the thermal environment are therefore liable to influence allostatic mediation of survival processes (e.g., immunity) during environmental challenges or stressors. However, the extent to which Tbody prompts individual variation in physiology remains largely unexplored in reptiles. Our study tested how circulating energy‐mobilizing hormone, energy metabolites, and immunity can var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 129 publications
(188 reference statements)
1
8
0
Order By: Relevance
“…These differences may be due to circadian rhythm, temperature, or activity level, all of which have been show to affect certain hematology and biochemistry analytes in other reptile species [ 13 , 22 , 76 – 79 ]. For example, the changes in heterophil and lymphocyte proportions are consistent with shifts seen in some reptile species as glucocorticoids increase [ 80 ], which in turn has been shown to vary with temperature [ 81 , 82 ] and diurnally [ 83 ]. Similarly, K and Ca may be secondarily affected by the demonstrated effects of temperature and activity-level on blood gas and acid-base status [ 77 , 79 , 84 ].…”
Section: Discussionmentioning
confidence: 64%
“…These differences may be due to circadian rhythm, temperature, or activity level, all of which have been show to affect certain hematology and biochemistry analytes in other reptile species [ 13 , 22 , 76 – 79 ]. For example, the changes in heterophil and lymphocyte proportions are consistent with shifts seen in some reptile species as glucocorticoids increase [ 80 ], which in turn has been shown to vary with temperature [ 81 , 82 ] and diurnally [ 83 ]. Similarly, K and Ca may be secondarily affected by the demonstrated effects of temperature and activity-level on blood gas and acid-base status [ 77 , 79 , 84 ].…”
Section: Discussionmentioning
confidence: 64%
“…In fact, we found no relationship between reactive bacterial killing ability and any tested covariate, suggesting that while baseline CORT is associated with baseline bacterial killing ability, baseline or reactive CORT may not predict how this specific measure of immunity changes after a stressful event. Other studies have also reported similar patterns where there is little ability to predict reactive bacterial killing ability in lizards or turtles (Neuman‐Lee & French, 2014; Refsnider et al, 2015), and other allostatic mediators and energy metabolites, such as glucose, may play a more important role (Hudson et al, 2020). Our predictions were based on studies of endotherms, and this suggests there is an unrealized understanding of immuno‐endocrine complexity ( e.g ., energetic tradeoffs) in reptiles, potentially due to the reptilian reliance on the innate immune system (Neuman‐Lee et al, 2015; Neuman‐Lee et al, 2019; Zimmerman, Paitz, et al, 2010; Zimmerman, Vogel, et al, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…In this SI, stress‐induced immunoenhancing effects were described for female cane toads ( Rhinella marina ), with increased post‐restraint antibody titers values (Assis et al, 2020). In accordance, restraint increased bacterial killing ability in plateau side‐blotched lizards ( Uta stansburiana uniformis ; Hudson et al, 2020). In the SI, a positive correlation between baseline corticosterone plasma levels and the bacterial killing ability has also been described for wild populations of western terrestrial gartersnake ( Thamnophis elegans ) and common gartersnake ( Thamnophis sirtalis ; Spence et al, in press).…”
Section: Stress‐induced Immunomodulationmentioning
confidence: 76%
“…Hudson et al (2020) also found immunoenhancing effects following restraint in plateau side‐blotched lizards; however, the bacterial killing ability was inversely related to the postrestraint corticosterone plasma levels. Besides, Billing et al (2020) bring a causative relation between corticosterone levels and immunity.…”
Section: Stress‐induced Immunomodulationmentioning
confidence: 96%